Comparison of efficacy and safety profile for home NB‐UVB vs. outpatient NB‐UVB in the treatment of non‐segmental vitiligo: A prospective cohort study. Issue 4 (25th March 2019) - Zhang, Li; Wang, Xiuxiu; Chen, Shujun; Zhao, Juemin; Wu, Jiaqiang; Jiang, Min; Zhang, Chengfeng; Xiang, Leihong
Summary: Objective: The aim of this study was to evaluate the efficacy and safety of home and outpatient narrowband ultraviolet B light (NB‐UVB) for the treatment of non‐segmental vitiligo. Methods: A total of 94 patients with non‐segmental vitiligo were enrolled. Forty‐eight patients were treated with home NB‐UVB, and the other 46 patients were treated with outpatient NB‐UVB over a period of 6 months. The efficacy, patient quality of life, and adverse events were assessed at month 3 and month 6 after treatment. Results: There was no significant difference in repigmentation and VASI‐reverse (VR) rates between outpatient NB‐UVB and home NB‐UVB groups. VR was higher in outpatient NB‐UVB group at month 3, and similar at month 6. For long‐standing vitiligo, VR was higher in the outpatient NB‐UVB group compared with home NB‐UVB group after 6 months of treatment. In recent vitiligo, the VR was similar between the two groups. Additionally, vitiligo‐specific health‐related quality‐of‐life instrument (VitiQoL) score was similar, and the adverse effects were minimal among the two groups. Conclusions: The efficacy and safety of home NB‐UVB and outpatient NB‐UVB phototherapy for non‐segmental vitiligo were comparable. According to our results, those with long‐standing vitiligo may be recommended to receive outpatient NB‐UVB phototherapy.